Levinas's Philosophy of Time : Gift, Responsibility, Diachrony, Hope - Severson, Eric R. (Book collections on Project MUSE., 2013)
"A chronological approach that examines the progression of Levinas's deliberations on time over six decades, thus providing new insights about aspects of Levinasian thought that have consistently troubled readers, including the differences between Levinas's early and later writings, his controversial invocation of the feminine, and the blurry line between philosophy and religion in his work"--Provided by publisher.